Antagonistic effect of endophytes against several root-rot pathogens of wheat - Tunali B.; Marshall D. (Durum wheat improvement in the Mediterranean region: New challenges, 2000)
Four different endophyte species were isolated from Rye grasses, Triticum spp. and Tall fescue. All Neotyphodium and Acremonium spp. significantly affected the growth rate of five root-rot pathogens of wheat in PDA plates. Culture filtrates of endophytes have had some effect against these test fungi. However nonfiltrated treatments are more efficient than culture filtrates. Conidia of A. typhinum and D. sorokiniana were mixed for germination test. The pathogen has shown abnormal elongation of the hypha, lysis of the conidia and abnormal germ tubes.
Seminar on Durum Wheat Improvement in the Mediterranean Region: New Challenges, 2000/04/12-14, Zaragoza (Spain)